A method for evaluating the quality service of a user unit in a water service company in Colombia (2020)
This research study proposes a method to evaluate the quality of service of a user service unit in a water service company in Colombia. Based on the theoretical foundation associated with the quality of service and the Six Sigma concept, service quality dimensions were identified to consolidate their valuation and to analyze the results in terms of defects per parts per million (DPMO), sigma level, and performance. It was found that the performance of the service quality dimensions was satisfactory due to the results obtained in all calculated metrics. The results showed that the user's attention center had an excellent performance during this research study. In conclusion, the present study provides a service quality evaluation method to the service sector in a public service company by using Six Sigma. © 2020 Centro de Informacion Tecnologica. All rights reserved.